Perfil clínico e qualidade de vida em pacientes com doença de Parkinson disfágicos - Carolina Campos Esteves (2018)
INTRODUCTION: Dysphagia is a prevalent symptom in Parkinson's disease (PD) and causes discontinuation of pleasure during meals, difficulty in maintaining hydration and nutrition, and social isolation. It can also impact negatively the patients' quality of life. However, it is not clear yet if this symptom is related to the diagnostic time and the severity of the disease, as well as the total daily dosage of levodopa. AIM: Evaluate the clinical profile of PD patients with dysphagia who do clinical monitoring at the Santa Casa/Belo Horizonte Centro de Especialidades Médicas (CEM), investigating the association of this symptom with the evolution of the disease, the PD severity of signs and symptoms, and the dosage of levodopa, and the impact on quality of life. MATERIALS AND METHODS: This is a cross-sectional observational study of patients diagnosed with idiopathic PD, who presented dysphagia after an initial screening using EAT-10 and SDQ. Cognitive indicators (MEEM), PD severity of signs and symptoms (UPDRS), severity of dysphagia (PARD and FOIS) and quality of life (SWAL-QOL) were included. For statistical analysis, it was applied SPSS version 21.0, with a significance level of p <0.05. RESULTS: Out of 44 participants, 21 (47,73%) were men with the average age of 69.4. The average PD diagnosed time was 6.1 years, and the patients had mixed profile type (rigid-akinetic). The SDQ was the most important instrument to detect dysphagia in the evaluated patients. Dysphagia was detected in patients in all stages of the disease; there was no association with the disease diagnosed time and the severity of signs and symptoms, except between the disease time and the FOIS. Common detected alterations findings in the sample were: positive cervical auscultation, which indicates laryngotracheal penetration or food accumulation in pharyngeal recess, multiple swallowing, increased oral transit time and reduced laryngeal elevation. Dysphagia measured by EAT-10, SDQ, PARD and FOIS has negatively impacted patients´ perception of quality of life. CONCLUSION: Dysphagia is a prevalent symptom in patients with PD in the CEM found since the early stages of the disease, regardless of the disease time and the severity of the clinical stages. The perception of patients' quality of life is negatively impacted by the severity of dysphagia in the evaluated patients.